Mengungkap Relationship Antara Interpersonal Closeness, Co-orientation and Complementarity Dalam Olahraga Pendakian Gunung - Ryan Abu Bakar; Yogi Akin; Mustika Fitri; Amung Ma’mun; Firman Septiadi (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
Current phenomena and facts that often occur are missing or accidents occur among mountain climbers, so that it becomes a major problem that needs to be evaluated in depth. The purpose of this study was to determine the role of interpersonal relationships Closeness, Co-orientation and Complementarity in mountain climbing sports. This study uses a qualitative approach through in-depth interviews. The subject of the study was the participants of climbing with AOPGI West Java on Mount Ciremay 3,078 masl in May 2021, totaling 54 people. The research sample was taken by purposive sampling by selecting experienced climbers who had climbed mountains above 3,000 meters above sea level 10 times, as many as 7 people were interviewed in this study. The results of the interview show that the role of the relationship in mountaineering is very necessary for closeness (closeness), Co-orientation (joint orientation) and Complementarity (complementary) to achieve success, safety and benefits from mountaineering. In the absence of a relationship, mountaineering becomes unpleasant, invites accidents and does not benefit from mountaineering.